Opinion and uptake of chloroquine for treatment of COVID-19 during the mandatory lockdown in the sub-Saharan African region - Osuagwu, U.L.; Nwaeze, O.; Ovenseri-Ogbomo, G.; Oloruntoba, Richard; Ekpenyong, B.; Mashige, K.P.; Timothy, C.; Ishaya, T.; Langsi, R.; Charwe, D.; Abu, E.K.; Chundung, M.A.; et al. (2021)
Background: As the search for effective treatment of coronavirus disease 2019 (COVID-19) infection continues, the public opinion around the potential use of chloroquine (CQ) in treating COVID-19 remains mixed. Aim: To examine opinion and uptake of CQ for treating COVID-19 in the sub-Saharan African (SSA) region. Setting: This study was conducted through an online survey software titled SurveyMonkey. Methods: Anonymous online survey of 1829 SSA countries was conducted during the lockdown period using Facebook, WhatsApp and authors' networks. Opinion and uptake of CQ for COVID-19 treatment were assessed using multivariate analyses. Results: About 14% of respondents believed that CQ could treat COVID-19 and of which, 3.2% took CQ for COVID-19 treatment. Multivariate analyses revealed that respondents from Central (adjusted odds ratios [aOR]: 2.54, 95% confidence interval [CI] 1.43, 4.43) and West Africa (aOR: 1.79, 95% CI 1.15, 2.88) had higher odds of believing that CQ could treat COVID-19. Respondents from East Africa reported higher odds for uptake of CQ for COVID-19 than Central, Western and Southern Africans. Knowledge of the disease and compliance with the public health advice were associated with both belief and uptake of CQ for COVID-19 treatment. Conclusion: Central and West African respondents were more likely to believe in CQ as a treatment for COVID-19 whilst the uptake of the medication during the pandemic was higher amongst East Africans. Future intervention discouraging the unsupervised use of CQ should target respondents from Central, West and East African regions.